Analysis of the effectiveness of asset-based community development in Beiji Village, Yogyakarta - Rusydi, Muhammad Akmal; Noer Yastuti, Fitria Tita; Shanjaya, Ichsan Rifqi; Sumegasari, Ema; Kurniasari, Cita; Ro'fah, Nella Inayatur; Widyastuti, Qory Jati; Ramadhan, Muhammad Lintang; Nugraha, Sofyan Adi; Listiya, Noor Bening; Ayu Saputri, Herlita Setya; Andhini, Dhea Nisa; Satya Nugraha, Muhammad Rizky; Safitri, Ananda Putri; Faisal, Fachrizal (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
Beji village holds significant potential related to local arts and culture that could be leveraged to achieve the status of a cultural pilot village. However, it faces substantial challenges, such as the lack of a dedicated venue for arts activities and insufficient cultural development. This study aims to analyse the effectiveness of the Asset-Based Community Development (ABCD) approach in empowering local arts and culture in Beji village. It employs a qualitative research design and a case study approach. Data collection techniques include observation, interviews, and documentation to gather in-depth information on the impact of this approach. The findings indicate that the ABCD approach successfully empowered the community by enhancing skills and preserving arts and culture through a series of programs designed by the PPKO Seni Rupa team, which also collaborated with various partners, including a program named Berbinar (Bersama Beji Bersinar). These findings are expected to provide valuable insights for practitioners and local government in designing more effective resource empowerment programs.